Structural insights into an atypical secretory pathway kinase crucial for Toxoplasma gondii invasion - Gaëlle Lentini (Nature Portfolio, 2021)
Host cell invasion by Toxoplasma gondii depends on the heavily phosphorylated RON complex, but the relevance and regulation of these modifications are not understood. Here, the authors identify the kinase RON13 as a key virulence factor, determine its structure and show that it phosphorylates the RON complex.